Cdk6’s functions are critically regulated by its unique C-terminus - Alessia Schirripa; Helge Schöppe; Sofie Nebenfuehr; Markus Zojer; Thorsten Klampfl; Valentina Kugler; Belinda S. Maw; Huriye Ceylan; Iris Z. Uras; Lisa Scheiblecker; Elisabeth Gamper; Ulrich Stelzl; et al. (iScience)
Summary: The vital cell cycle machinery is tightly regulated and alterations of its central signaling hubs are a hallmark of cancer. The activity of CDK6 is controlled by interaction with several partners including cyclins and INK4 proteins, which have been shown to mainly bind to the amino-terminal lobe. We analyzed the impact of CDK6’s C-terminus on its functions in a leukemia model, revealing a central role in promoting proliferation. C-terminally truncated Cdk6 (Cdk6 ΔC) shows reduced nuclear translocation and therefore chromatin interaction and fails to enhance proliferation and disease progression. The combination of proteomic analysis and protein modeling highlights that Cdk6’s C-terminus is essential for protein flexibility and for its binding potential to cyclin D, p27Kip1 and INK4 proteins but not cyclin B. We demonstrate that the C-terminus is a unique and essential part of the CDK6 protein, regulating interaction partner binding and therefore CDK6’s functionality.